Little Cash, Little Carry: Liquidity Constraints and Missing Out on Bulk Discounts in Tanzania. - Olabisi, Michael; Persaud, Alexander (Journal of Development Studies, 2026)
Using high-frequency data on households' item-level purchases from Tanzania, we show that liquidity constraints keep the poor from using bulk discounts consistently. On average, households save roughly 20% during the 'flush' days of the month, which comes from buying in bulk, and the poorest save over 30%. Relaxing liquidity constraints through wage income or higher wealth leads to lower prices paid overall and a lower drop when flush. We estimate that failing to use bulk discounts costs households at the first quartile of wealth an additional 1% of their spending on food relative to households at the third quartile.